2022
DOI: 10.1155/2022/4388919
|View full text |Cite
|
Sign up to set email alerts
|

FAT10 Combined with Miltefosine Inhibits Mitochondrial Apoptosis and Energy Metabolism in Hypoxia-Induced H9C2 Cells by Regulating the PI3K/AKT Signaling Pathway

Abstract: Hypoxia-induced cardiomyocyte apoptosis is the main contributor to heart diseases. Human leukocyte antigen F-associated transcript 10 (FAT10), the small ubiquitin-like protein family subtype involved in apoptosis, is expressed in the heart and exhibits cardioprotective functions. This study explored the impact of FAT10 on hypoxia-induced cardiomyocyte apoptosis and the involved mechanisms. The cardiomyocyte cell line H9C2 was cultivated in hypoxia-inducing conditions (94% N2, 5% CO2, and 1% O2) and the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This suggested that the activation of FAT10-mTORC1 signaling pathway caused by loss of Celf2 is independent to the MA9-DOT1L signaling pathway. FAT10 belongs to the ubiquitin-like protein family and was demonstrated to be able to increase AKT phosphorylation, and thereby activate the mTORC1 signaling pathway [43][44][45][46]. In Yan's study, FAT10 was shown to activate AKT signaling by stabilizing EGFR in bladder cancer cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the activation of FAT10-mTORC1 signaling pathway caused by loss of Celf2 is independent to the MA9-DOT1L signaling pathway. FAT10 belongs to the ubiquitin-like protein family and was demonstrated to be able to increase AKT phosphorylation, and thereby activate the mTORC1 signaling pathway [43][44][45][46]. In Yan's study, FAT10 was shown to activate AKT signaling by stabilizing EGFR in bladder cancer cells [44].…”
Section: Discussionmentioning
confidence: 99%